Ultrasmall alloy nanozyme for ultrasound- and near-infrared light-promoted tumor ablation - Jana, Deblin (2022)
The therapeutic effect of chemodynamic therapy (CDT) is significantly restricted by the stern reaction conditions and slow reaction rate of the Fenton reaction (pH 3-4). Herein, we report an ultrasmall trimetallic (Pd, Cu and Fe) alloy nanozyme (PCF-a NEs) possessing dynamic active-site synergism, thus exhibiting a cascade glutathione peroxidase and peroxidase (POD) mimicking activities in circumneutral pH. PCF-a NEs exhibit photothermally augmented POD property and high photothermal conversion efficiency (62%) for synergistic tumor cell apoptosis. In addition, ultrasound can also enhance the mass transfer at active catalytic sites of PCF-a NEs, in turn accelerating Fenton-like reaction for tumor-specific CDT. This work provides a strategy for engineering alloy nanozymes in a bioinspired way for the amplification of intratumor reactive oxygen species in response to external stimuli, demonstrating enhanced efficiency for the inhibition of tumor growth in vitro and in vivo.